Evaluation of company performance by simulation - (:unkn) unknown (My University, 2007)
Simulation is the most widely used management science and operations research technique employed by industry and government. In its broadest sense, computer simulation is the process of designing a mathematical-logical model of a real system and experimenting with this model on a computer. This paper is based on the system simulation of a company in which several kinds of electronic instruments are repaired. System of the company is observed and necessary data is collected in one year. Working system of the company is modeled and simulated by the ARENA software for academic purposes. Simulations for alternative models are run several times in order to improve system performance. Impressive improvements in system operations have been obtained by employing the simulation model for planning purposes. Using the estimated performances from simulation outputs, system performance is increased approximately 40% and total annual income which is calculated manually of the company is increased from $473067.768 to $972321.676.
Keywords: ARENA; Simulation; System cost; System performance